Artificial Intelligence, Reciprocal Symmetry, and Customer Relationship Management: A Paradigm Shift in Business - Mullangi, Kishore; Maddula, Sai Sirisha; Shajahan, Mohamed Ali; Sandu, Arun Kumar (Asian Business Review, 2018)
This article examines how combining reciprocal symmetry, artificial intelligence (AI), and customer relationship management (CRM) might change corporate paradigms and promote long-term growth. Investigating the convergence of AI and reciprocal symmetry principles within CRM, examining AI’s role in fostering customer-centric relationships, and identifying policy implications for responsible AI use in business practices are the main goals of this study. This study’s methodology uses a secondary data-based review strategy to synthesize industry reports, academic publications, and current literature to analyze the conceptual framework and real-world applications of AI-driven CRM tactics integrated with the concepts of reciprocal symmetry. Important discoveries show that combining reciprocal symmetry and AI improves personalization, encourages team-based innovation, and puts customers’ needs first in CRM. However, to guarantee safe AI adoption in commercial contexts, issues like data privacy consequences and ethical considerations highlight the necessity for explicit regulations and guidelines. The policy implications underscore the significance of formulating legislation that protects consumer rights, encourages ethical AI implementation, and sets benchmarks for AI-powered CRM procedures. The study highlights the potential of artificial intelligence (AI) and reciprocal symmetry to drive a paradigm shift in corporate relationships and innovation towards a customer-centric approach.